CD20-positive peripheral T-cell lymphoma not otherwise specified: a case series and review of the literature - Zhou, Pan; Wang, Lifu; Pei, Xiaohang; Yang, Liu; Zhou, Yunmeng; Ma, Rongjun; Chen, Yuqing; Zhu, Zunmin; Yuan, Xiaoli (Frontiers in Oncology, 2025)
Peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) is a heterogeneous and aggressive malignancy that usually lacks B-cell associated antigens. Here, we identified three cases of PTCL-NOS that uniformly expressed T-cell specific antigens (CD2 and CD3) and the B marker CD20 (CD20+ PTCL-NOS). Molecular studies showed clonal rearrangement of the chain T-cell receptor genes without evidence of a clonal rearrangement of the immunoglobulin gene. All three patients were diagnosed with the advanced stages and had bone marrow (BM) involvement, of which one patient was confirmed by PET-CT and the other two patients were confirmed by BM biopsy. However, we surprisingly found that BM-infiltrated lymphoma cells did not express CD20. Whole-exome sequencing analysis revealed that the most common mutations were on the DDX3X and TET2 genes. Although all the patients had relatively low Ki67 indices, they achieved poor response to the first-line treatment with CHOP-like chemotherapy. Subsequently, one patient was treated at a local hospital with an unspecified regimen, and the other two patients ultimately received rituximab combined chemotherapy as a salvage treatment after receiving multiple second-line therapies. However, the outcomes of these patients remained unsatisfactory. Therefore, it currently appears to be quite challenging to provide appropriate and effective treatment for patients with CD20+ PTCL-NOS.